KANDUNGAN GIZI, INDEKS GLIKEMIK DAN BEBAN GLIKEMIK MARSHMALLOW KULIT BUAH NAGA (HYLOCEREUS POLYRHIZUS) DENGAN PENAMBAHAN BAYAM MERAH - Agung Kurniawan (2020)
The prevalence of diabetes mellitus in 2018 an increase of 0.5% from 2013. The impact of diabetes mellitus can be prevented by eating foods that contain fiber, antioxidants, have a low GI value and low glycemic load. Examples of such foods are the skin of dragon fruit, red spinach and stevia sugar. This study aims to determine the nutritional content, glycemic index and glycemic load of dragon fruit peel marshmallows with the addition of red spinach. This study uses an experimental research design and descriptive analysis method. Organoleptic test was processed using the Kruskal Wallis test and test using the Mann-Whitney test. Kruskal Wallis test results showed the substitution of stevia sugar proved significantly (p <0.05) against the hedonic quality test and hedonic test. The selected formula is determined using the exponential replacement method (MPE) based on the parameters of color, aroma, texture, and taste with the result of the selected formula is formula 1 with a substitution of 15% stevia sugar. Formula 1 contains 35.25% water content, 1.66% ash content, 5.5% protein content, 0.67% fat content, 57.45% carbohydrate content. The glycemic index value of marshmallow dragon fruit peel with the addition of red spinach is 87.29 high, while the glycemic load of is17.54 which is in medium category. The prevalence of diabetes mellitus in 2018 an increase of 0.5% from 2013. The impact of diabetes mellitus can be prevented by eating foods that contain fiber, antioxidants, have a low GI value and low glycemic load. Examples of such foods are the skin of dragon fruit, red spinach and stevia sugar. This study aims to determine the nutritional content, glycemic index and glycemic load of dragon fruit peel marshmallows with the addition of red spinach. This study uses an experimental research design and descriptive analysis method. Organoleptic test was processed using the Kruskal Wallis test and test using the Mann-Whitney test. Kruskal Wallis test results showed the substitution of stevia sugar proved significantly (p <0.05) against the hedonic quality test and hedonic test. The selected formula is determined using the exponential replacement method (MPE) based on the parameters of color, aroma, texture, and taste with the result of the selected formula is formula 1 with a substitution of 15% stevia sugar. Formula 1 contains 35.25% water content, 1.66% ash content, 5.5% protein content, 0.67% fat content, 57.45% carbohydrate content. The glycemic index value of marshmallow dragon fruit peel with the addition of red spinach is 87.29 high, while the glycemic load of is17.54 which is in medium category.